2015
DOI: 10.1093/hmg/ddu751
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of smoking-induced genome-wide methylation changes with time since smoking cessation

Abstract: Several studies have recently identified strong epigenetic signals related to tobacco smoking. However, an aspect that did not receive much attention is the evolution of epigenetic changes with time since smoking cessation. We conducted a series of epigenome-wide association studies to capture the dynamics of smoking-induced epigenetic changes after smoking cessation, using genome-wide methylation profiles obtained from blood samples in 745 women from 2 European populations. Two distinct classes of CpG sites w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

27
296
3
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 270 publications
(327 citation statements)
references
References 41 publications
27
296
3
1
Order By: Relevance
“…Regarding overall rates of reversion of disturbed methylation over time, it is of debate as to whether the relative persistence of differential methylation following cessation for certain CpG sites is due to slower reversion rates, or comparable reversion rates but a larger initial disturbance in methylation [8,20]. Our results indicate the rate at which the methylation levels change in FS is related to the difference in methylation to NS, implying perhaps a type of exponential decay in the difference in methylation after cessation.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Regarding overall rates of reversion of disturbed methylation over time, it is of debate as to whether the relative persistence of differential methylation following cessation for certain CpG sites is due to slower reversion rates, or comparable reversion rates but a larger initial disturbance in methylation [8,20]. Our results indicate the rate at which the methylation levels change in FS is related to the difference in methylation to NS, implying perhaps a type of exponential decay in the difference in methylation after cessation.…”
Section: Discussionmentioning
confidence: 75%
“…Previous evaluations of the effect of time since smoking cessation have revealed CpG sites that could be classified as reversible and sites that could be classified as persistently differentially methylated [8,[18][19][20]. Reversible sites are those that are differentially methylated between smokers and non-smokers but with the difference disappearing some time after cessation of smoking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 The study of Beineke et al 31 reported up-regulation of LRRN3, PID1, GPR15 and FUCA1 gene expression in the whole blood of current smokers with LRRN3 being the most statistically significant gene. In a recent study by Guida et al, 33 CpG sites at both LRRN3 and GPR15 were found to be hypomethylated in blood. LRRN3 is particularly interesting because it has been shown to be over-expressed in current smokers and in the study by Guida et al, 33 it was the only gene associated with smoking at the level of both methylation and gene expression.…”
Section: Discussionmentioning
confidence: 89%
“…In a recent study by Guida et al, 33 CpG sites at both LRRN3 and GPR15 were found to be hypomethylated in blood. LRRN3 is particularly interesting because it has been shown to be over-expressed in current smokers and in the study by Guida et al, 33 it was the only gene associated with smoking at the level of both methylation and gene expression. In genetic association studies, variants in PID1 have been associated with lung function in the Korean population.…”
Section: Discussionmentioning
confidence: 89%